The effect of hyoscine n- butylbromide on labor progress: A systematic review - Zaynab Mohaghegh; Parvin Abedi; Shahla Faal; Shayesteh Jahanfar; Alayna Surdock; Foruzan Sharifipour; Maryam Zahedian (BMC, 2020)
Abstract Background The objective of this systematic review and meta-analysis was to assess the effectiveness of hyoscine n-butylbromide in labor progress. Methods The databases including PubMed, the Cochrane Library, Science-Direct, Scopus and Web of Science were searched for studies published up to December 2019. Articles that published as randomized controlled trials (RCTs), and full-text articles published in English or other languages were included and participants were primi or multigravida women who were in active phase of labor. The intervention included HBB compared to placebo (normal saline) that was used during active phase of labor. Pooled estimates were measured using the fixed or random effect model, while the overall effect was reported in a mean difference (MD). All data were analyzed using Review Manager 5.3. Results Twenty studies involving 3108 women were included in meta-analysis. Based on subgroup analysis by parity, use of HBB significantly reduced the duration of the first stage of labor in primigravida women (MD = − 57.73; 95% CI: [− 61.48, − 53.60]) and in multigravida women (MD = − 90.74; 95% CI: [− 97.24, − 84.24]). Administering HBB could reduce the second stages of labor in primigravidas and multigravidas about 6 min and 4 min respectively. Also, HBB reduced the duration of the third stage of labor in multigravidas about 3 min. APGAR score at one and 5 min after birth was not affected. The main maternal adverse effect was tachycardia and dry mouth. Labor duration in studies in which the participants were primi-and multigravida was not presented based on separate parities except for four papers, and the route of HBB administration was not the same across all studies. Conclusions Although, the effect of HBB was minimal when multigravidas and primigravidas women were considered together, the HBB was clinically effective in primigravida and multigravida women for shortening the first and the second stages of labor. Also, HBB could reduce the length of the third stage of labor in multigravidas.